2018
DOI: 10.1039/c7sc01996c
|View full text |Cite
|
Sign up to set email alerts
|

Unequivocal determination of caulamidines A and B: application and validation of new tools in the structure elucidation tool box

Abstract: Newly described NMR experimental approaches can provide valuable structural details and a complementary means of structure verification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 49 publications
0
62
0
Order By: Relevance
“…Over the past few years, our group has been involved in several internal projects and external collaborations that necessitated the acquisition of 1,1‐ADEQUATE spectra on different classes of small molecules ranging from natural products to synthetic molecular structures . The present study is a follow‐up to previous studies in which we have observed multiple‐bond correlations “leaking” into 1,1‐ADEQUATE spectra due to unusually large 2 J CC and 3 J CC couplings for particular structural motifs that can be nearly as large as some 1 J CC couplings .…”
Section: Introductionmentioning
confidence: 67%
“…Over the past few years, our group has been involved in several internal projects and external collaborations that necessitated the acquisition of 1,1‐ADEQUATE spectra on different classes of small molecules ranging from natural products to synthetic molecular structures . The present study is a follow‐up to previous studies in which we have observed multiple‐bond correlations “leaking” into 1,1‐ADEQUATE spectra due to unusually large 2 J CC and 3 J CC couplings for particular structural motifs that can be nearly as large as some 1 J CC couplings .…”
Section: Introductionmentioning
confidence: 67%
“…Subsequently, the PBLG structure was energyminimized and equilibrated in a chloroform box using the molecular simulation software GROMACS. [13] P3D was evaluated on the basis of RDCs measured for six small molecules dissolved in chloroform and weakly aligned by PBLG: the fungicidal cyclopentenone 4,6-diacetylhygrophorone A (DAHPA), [14] isopinocampheol (IPC), [12a] the alkaloids strychnine and caulamidine, [15] [16] and the lactone parthenolide. [12b] The six small molecules have different numbers of (relative) stereoisomers, ranging from 4 for DAHPA to 16 for parthenolide (see Figures S1-S6 in the Supporting Information).…”
mentioning
confidence: 99%
“…In the last few years, the application of quantum mechanical (QM) predictions has been gaining a considerable attention by the scientific community for high accuracy in the reproduction of the experimental NMR properties even at low levels of theory and thanks to the increasing computational power. This hybrid approach has been demonstrated as a valuable method for the structural studies of organic compounds, spanning from configurational and conformational assignments to structure elucidation of natural products. The use of QM‐NMR integrated strategy is not limited to stereostructural studies but could support the total synthesis of natural compounds and also the analysis of ligand–macromolecule interactions.…”
Section: Introductionmentioning
confidence: 99%